Accounting students’ association FinEASE: next-gen financial tracking for future accounting leaders - Burhanuddin, Muhammad Sufi; Azli, Muhammad Zaqwan Shaiful; Baharim, Nur Arifah; Mohamad Nazarudin, Nurin Batrisyia Akmal; San, Suzana (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The Accounting Students Association for Bachelor of Accounting students at UiTM Cawangan Kelantan is known as Members of Bachelor in Accountancy Society (MemBACCs). MemBACCs plays a significant role in organizing activities for its members and managing financial records. The treasurer had previously used a cash book to record the income and expenditure, which caused difficulties in ensuring accurate transactions tracking, the risk of human errors and reducing transparency of financial records. Additionally, it can be lost or damaged and time- consuming for manual updates. To address these issues, this project proposed transitioning to a financial tracking system using Microsoft Excel for better accuracy and traceability of financial records. Unlike cash book methods, the system can minimize human errors as it is automated calculation, easy to manage the financial records and cost-effective alternative to accounting software. In addition, the financial tracking system using Microsoft Excel has the potential to be adapted for other student associations and small business owners. Thus, MemBACCs could provide consultancy fees and charge a fee for training sessions. Ultimately, it contributes to the accuracy and transparency of financial records and generates income for MemBACCs.